Prevalence of Obesity in Adolescent and Related Risk Factor in Surat City - Prasad, Rajiv; Vaghela, Vibhuti D; Kuvadiya, Hina; Labana, Yogesh (National Journal of Community Medicine, 2018)
Background: Obesity is one of the most widespread and a major problem affecting children and adolescents is of global nutritional concern. Obesity is multifactorial disease prevalence and risk factor varies according to place, race, genetics, cultural practices, food habits and economic status. Objectives: To assess prevalence and identify probable risk factors for of obesity and overweight in high school children of Surat. Methods: This Cross-sectional study was conducted among adolescent students. Students were divided in overweight & obese and normal based on BMI. Both the groups were compared based on socio-demographic profile and risk factors like dietary history, physical activity, family history of HT, DM and obesity, etc. Results: In our study the overall prevalence of obesity is 7.4% and overweight is 9.9%. Overweight and obesity was significantly associated with more expected calorie intake, frequent restaurant visits, regular consumption of fast food/ junk food, sedentary activities, using bus/car/auto as a transportation for going to school, upper and upper middle socioeconomic class, family history of diabetes mellitus, obesity and hypertension (P value <0.001). Conclusion: The prevalence of obesity is increasing due affluent lifestyle.